Biosafety samples (sperm, oocytes and embryos person) during prolonged storage in liquid nitrogen - Ye. V. Petrova; N. P. Makarova; L. F. Kurilo (Андрология и генитальная хирургия, 2014)
Cryopreservation of sperm, oocyte and embryo plays an important role in modern assisted reproductive technologies. To date the only available source of low temperatures satisfying the conditions of long-term storage of cells is liquid nitrogen. However there is a possibility of transmission of infectious agents between samples in liquid nitrogen at their co-location in a cryostorage. The article discusses ways to reduce the risk of cross-contamination and the integrated approach to biosecurity.